Predictors of consistent condom use among Portuguese women attending family planning clinics - Cunha Veiga Costa, Eleonora (2015)
Women account for 30% of all AIDS cases reported to the Health Ministry in Portugal and most infections are acquired through unprotected heterosexual sex with infected partners. This study analyzed socio-demographic and psychosocial predictors of consistent condom use and the role of education as a moderator variable among Portuguese women attending family planning clinics. A cross-sectional study using interviewer-administered fully structured questionnaires was conducted among 767 sexually active women (ages 18–65). Logistic regression analyses were used to explore the association between consistent condom use and the predictor variables. Overall, 78.7% of the women were inconsistent condom users. The results showed that consistent condom use was predicted by marital status (being not married), having greater perceptions of condom negotiation self-efficacy, having preparatory safer sexual behaviors, and not using condoms only when practicing abstinence. Living with a partner and having lack of risk perception significantly predicted inconsistent condom use. Less educated women were less likely to use condoms even when they perceive being at risk. The full model explained 53% of the variance in consistent condom use. This study emphasizes the need for implementing effective prevention interventions in this population showing the importance of taking education into consideration.